PENGARUH MASA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI DESA SAMUDRA DAN SAMUDRA KULON - Sugito, Sugito; Suyitno, Y; Kuntoro, Kuntoro (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research aims to identify: 1) the influence of working time on teacher performance, 2) the influence of motivation on teacher performance, and 3) the influence of working time and motivation on performance of elementary school teachers in the villages of Samudra and Samudra Kulon. This research is ex-post facto looking for causal relationships, to reveal facts based on measurements of symptoms that have occurred in each respondent. Determination of the sample in this study is a saturated sample, where all members of the population become the object of research. Total population is 50 people. The analysis carried out was a simple and multiple correlation analysis and regression analysis. Respondents in this research have a working time of 2 to 32 years. The results of this research are (1) there is a negative influence on the working time variable on teacher performance; (2) there is a positive influence on the motivation variable on teacher performance; and (3) there is a positive influence on working time and motivation on performance. The effective contribution of working time and motivation to performance are 8.9% and 18%, respectively. The relative contribution of working time and motivation to performance are 33% and 67%, respectively.